2013
DOI: 10.1118/1.4851555
|View full text |Cite
|
Sign up to set email alerts
|

Metallic artifact mitigation and organ-constrained tissue assignment for Monte Carlo calculations of permanent implant lung brachytherapy

Abstract: Despite producing differences in CT images, dose metrics calculated using the STR, fan beam + STR, and 3D median filter techniques produce similar dose metrics. Results suggest that the accuracy of dose distributions for permanent implant lung brachytherapy is improved by applying lung-constrained tissue assignment schemes to metallic artifact corrected images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 42 publications
(60 reference statements)
0
19
0
Order By: Relevance
“…Several researchers have developed different algorithms to remove these artifacts. [20][21][22][23] These approaches use model-based iterative reconstruction (MBIR), with modern CT imaging modalities to correct artifacts within the sinogram. The model corrects for metallic artifacts by subtracting reprojected sinograms of segmented brachytherapy seed images from the raw sinogram.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have developed different algorithms to remove these artifacts. [20][21][22][23] These approaches use model-based iterative reconstruction (MBIR), with modern CT imaging modalities to correct artifacts within the sinogram. The model corrects for metallic artifacts by subtracting reprojected sinograms of segmented brachytherapy seed images from the raw sinogram.…”
Section: Introductionmentioning
confidence: 99%
“…28 Earlier work has shown that the accuracy of dose calculations can be significantly diminished without first implementing a metallic artifact reduction algorithm to post-implant CT images. [29][30][31] Artifact mitigation in CT images has been studied in the context of dental fillings 28,32,33 and prosthesis, [34][35][36][37] and several general approaches including thresholding, 29,30 spatial filters 30,38 and sinogram space filters [29][30][31]39 have been proposed. No published arifact mitigation method has been shown to work perfectly with the artifacts characteristic of brachytherapy images, and it remains unclear how differences in artifact mitigation approaches affect dose calculations.…”
Section: Model Based Dose Calculationsmentioning
confidence: 99%
“…This smoothing effect could challenge preservation of soft tissue heterogeneities important for other treatment sites such as breast 47,48 or lung. 29,30 The 3D median filter is one of several spatial-domain filters which could be applied to mitigate artifacts from CT images. We have explored other similar methods, such as Gaussian filters, 2D and 3D filters, varied kernel and clip sizes, and have consistently observed comparative blurring effects.…”
Section: Dose Distributionsmentioning
confidence: 99%
See 2 more Smart Citations